Enduring uncertainty : deportation, punishment and everyday life - Hasselberg, Ines (2016)
Focusing on the lived experience of immigration policy and processes, this volume provides fascinating insights into the deportation process as it is felt and understood by those subjected to it. The author presents a rich and innovative ethnography of deportation and deportability experienced by migrants convicted of criminal offenses in England and Wales. The unique perspectives developed here – on due process in immigration appeals, migrant surveillance and control, social relations and sense of self, and compliance and resistance – are important for broader understandings of border control policy and human rights.This title was made Open Access by libraries from around the world through Knowledge Unlatched.